Effect of the quantum learning model on attitude, anxiety, curiosity, academic achievement and retention in science course - Uyanık, Gökhan; Özdemir Uyanık, Rüya (Pedapub, 2024)
The aim of this research was to examine the effect of quantum learning model on students' attitudes, curiosity and anxiety towards science course and its effect on their academic achievement and retention of success. A pretest-posttest control group quasi-experimental design was used in this research. The research was conducted in fall semester of 2019-2020 academic year at a public school in Kastamonu/Turkey. The study group of research consisted of a total 58 students, including experimental and control groups. Science Curiosity Scale, Science Anxiety Scale, Attitude Scale and Achievement Test were used as data gathering tools. In the analysis of data, independent t-test was applied to determine the difference between groups. When the findings were examined, it was determined that there was not a significant difference between the curiosity scale pre-test scores of experimental and control groups. However, according to curiosity scale post-test results after experimental application, it was determined that there was a significant difference in favor of experimental group. It was determined that there was not a significant difference between the anxiety scale pre-test scores of experimental and control groups. However, according to the anxiety scale post-test results after experimental application, it was determined that there was a significant difference in favor of experimental group. It was determined that there was not a significant difference between science attitude scale both pre-test and post-test scores of experimental and control groups. While there was not a statistically significant difference between the academic achievement test pre-test scores of experimental and control group students, it was determined that the difference between post-test scores was significant in favor of experimental group. In addition, according to the results of retention test, it was determined that there was a significant difference between the scores of experimental and control groups in favor of experimental group.